Fire risk assessment of heritage building - perspectives of building stakeholders - Ibrahim, Md. Najib; Yahya, Mohamad Ridzuan; Mohd. Din, Azrin; Mohd. Yunus, Rodzyah; Ibrahim, Mohd. Sharifuddin; Ali, Maisarah (2013)
Heritage building is very important in preserving the culture and to the tourism potential. Hence, the proper budget allocation to the prevention of fire loss is critical. Budget allocation is normally based on fire risk assessment. The assessment is interpreted based on the perception of stakeholders. Using structured interview and analytic hierarchy process (AHP) this study identifies and explains the diversity of fire risk perception of stakeholders